Novel-structured electrospun TiO2/CuO composite nanofibers for high efficient photocatalytic cogeneration of clean water and energy from dye wastewater - Lee, Siew Siang (2013)
It is still a challenge to photocatalytically cogenerate clean water and energy from dye wastewater owing to the relatively low photocatalytic efficiency of photocatalysts. In this study, novel-structured TiO2/CuO composite nanofibers were successfully fabricated via facile electrospinning. For the first time, the TiO2/CuO composite nanofibers demonstrated multifunctional ability for concurrent photocatalytic organic degradation and H2 generation from dye wastewater. The enhanced photocatalytic activity of TiO2/CuO composite nanofibers was ascribed to its excellent synergy of physicochemical properties: 1) mesoporosity and large specific surface area for efficient substrate adsorption, mass transfer and light harvesting; 2) red-shift of the absorbance spectra for enhanced light utilization; 3) long nanofibrous structure for efficient charge transfer and ease of recovery, 4) TiO2/CuO heterojunctions which enhance the separation of electrons and holes and 5) presence of CuO which serve as co-catalyst for the H2 production. The TiO2/CuO composite nanofibers also exhibited rapid settleability by gravity and uncompromised reusability. Thus, the as-synthesized TiO2/CuO composite nanofibers represent a promising candidate for highly efficient concurrent photocatalytic organic degradation and clean energy production from dye wastewater.